Synthesis, structure and antimicrobial activity of substituted chalcones and their derivatives - Ibrayev, M.K.; Akhmetova, S.B.; Takibayeva, A.T.; Issabayeva, M.B.; Nurkenov, A.O.; Seilkhanov, О.T. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the paper the interaction reactions of the hydroxyl substituted acetophenones with the substituted aromatic aldehydes in the presence of aqueous alcoholic solution of alkali (Claisen-Schmidt condensation), which is as aldol condensation were given. This reaction has a big duration and comes to the end within 62–85 h. The final product contains double bonds in α,β-position to carbonyl group. Further functionalization of the chalcones obtained was performed by their correlation with hydrazine hydrate. It was found that boiling of chalcones with hydrazine hydrate in ethanol led to an intramolecular cyclocondensation of an intermediate hydrazone to form some pyrazole derivatives. Structures of the synthesized compounds were studied with 1H and 13C-NMR spectroscopy, and data on two-dimensional (1H-1H) COSY and (1H-13C) HMQC spectra. Values of the chemical shifts, multiplicity and integral intensity of signals in one-dimensional 1H and 13C NMR spectra were determined. Homo- and heteronuclear interactions confirming structure of the compounds studied were determined with (1H-1H) COSY and (1H-13C) HMQC spectra. Data on the antimicrobial activity of the synthesized chalcones, pyrazolines and flavonones were showed. It was found that all studied substances practically showed a weak antibacterial activity. Exception is S. aureus culture, which possess the moderate actions for compounds of (E)-1.3-bis (2-hydroxyphenyl)-prop-2-en-1-one, (E)-1-(2-hydroxyphenyl)-3-(4-hydroxyphenyl)-prop-2-en-1-one,(E)-3-(ethoxy-4-hydroxyphenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one and 2-(2-hydroxyphenyl) flavone.
Ауыстырылған халкондардың және олардың туындыларының синтезі, құрылымы және микробқа қарсы белсенділігі
Синтез, структура и антимикробная активность замещенных халконов и их производных
Keywords: substituted aromatic aldehyde; chalcone; pyrazoline; flavonone; cytokine; NF-κB transcription factor